2014
DOI: 10.2147/bctt.s69416
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HER2 testing patterns, HER2+ disease, and the utilization of HER2-directed therapy in early breast cancer

Abstract: ContextDetermining human epidermal growth factor receptor 2 (HER2) status is critical for the management of early-stage breast cancer (ESBC). An understanding of HER2 testing practices can provide insight into how test results influence the use of HER2-directed therapy.ObjectiveTo assess HER2 testing, HER2+ disease, and HER2-directed therapy in ESBC at the Huntsman Cancer Institute before and after the 2007 American Society of Clinical Oncology and College of American Pathologist (ASCO/CAP) guidelines on HER2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…19 Observational studies on real-world treatment patterns in patients diagnosed with and/or treated for HER2 þ EBC between 2005 and 2015 suggest that 19.1% to 59.5% in the United States, Canada, Australia, New Zealand, United Kingdom, The Netherlands, Germany, and China did not receive neoadjuvant or adjuvant trastuzumab (Table 1). [23][24][25][30][31][32][34][35][36][37][39][40][41]44,45 Use of trastuzumab was somewhat less in patients with small ( 1 cm) and/or node-negative HER2 þ tumors, 28,30,40,41,44 in whom the benefits of adjuvant trastuzumab therapy are somewhat controversial. 7,9,10 Several studies conducted between 2006 and 2013 also suggest that older patients with HER2 þ EBC and patients with HER2 þ /hormone receptor (HR)-positive disease were less likely to receive trastuzumabbased therapy (Table 1).…”
Section: Patterns Of Use In Ebcmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Observational studies on real-world treatment patterns in patients diagnosed with and/or treated for HER2 þ EBC between 2005 and 2015 suggest that 19.1% to 59.5% in the United States, Canada, Australia, New Zealand, United Kingdom, The Netherlands, Germany, and China did not receive neoadjuvant or adjuvant trastuzumab (Table 1). [23][24][25][30][31][32][34][35][36][37][39][40][41]44,45 Use of trastuzumab was somewhat less in patients with small ( 1 cm) and/or node-negative HER2 þ tumors, 28,30,40,41,44 in whom the benefits of adjuvant trastuzumab therapy are somewhat controversial. 7,9,10 Several studies conducted between 2006 and 2013 also suggest that older patients with HER2 þ EBC and patients with HER2 þ /hormone receptor (HR)-positive disease were less likely to receive trastuzumabbased therapy (Table 1).…”
Section: Patterns Of Use In Ebcmentioning
confidence: 99%
“…Few studies in patients with EBC, and none in patients with MBC, reported reasons for patients not receiving anti-HER2 therapy. 23,25,30,32,36,37,40,44 Furthermore, it is not clear how often HER2 blockade is continued in multiple lines of systemic therapy for metastatic disease. In the adjuvant setting (Table 1), trastuzumab was withheld from patients because of advanced age (11%-23%), increased risk of cardiac toxicity (15%-46.4%), or other comorbidities (approximately 12%).…”
Section: Reasons For Patients Not Receiving Anti-her2 Therapymentioning
confidence: 99%
“…Because these two chemotherapy drugs are used sequentially or combined with other chemotherapy drugs, clinical studies have not been planned. In the literature, erlotinib and imatinib dependent ototoxicity have been reported, as they are tyrosine kinase inhibitors that effect ototoxicity along a different pathway [1,6,9] . When we examine the studies relating tyrosine kinase inhibitors to hearing loss, many of them displayed mechanisms related to EGFR and HER [10,11] .…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab is a humanized recombinant monoclonal antibody that acts on the extracellular portion of the HER2 protein [1] . Lapatinib (Tykerb®; Glaxo-Smith Kline) is a tyrosine kinase inhibitor that suppresses epidermal growth factor 1 (EGF-1) and intracellular phosphorylation of the HER-2/neu receptor.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 HER2 is also known as HER2/neu, erbB-2, or EGFR2 [67]. This cellular receptor may contribute to the growth and/or dissemination of certain types of tumors [14,67,68]. HER2 overexpression is found in 20% of patients with breast cancer [13,69,71].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%